Effect of Aerated and Non-Aerated Compost Tea at Different Concentrations on Early Growth of Maize (Zea mays L.) - Rachmandhika, Yusuf; Muhlison, Wildan; Sucipto, Irwanto; Pusparani, Syafina; Saputra, Tri Wahyu; Ristiyana, Suci (International Journal on Food, Agriculture and Natural Resources, 2025)
Declining soil fertility caused by the continuous use of chemical fertilizers has encouraged the development of sustainable and environmentally friendly nutrient management strategies. Compost tea, a liquid extract derived from mature compost, has gained attention due to its potential to supply readily available nutrients and beneficial microorganisms. This study aimed to evaluate the compost tea production process and assess the effects of aerated compost tea (ACT) and non-aerated compost tea (NACT) at different application concentrations on the early growth of maize (Zea mays L.). The experiment was conducted under controlled conditions in November 2025 using maize as the test plant. Compost tea was prepared by extracting mature compost in water at a ratio of 1:5, with aeration applied for ACT and without aeration for NACT over a three-day fermentation period. Treatments consisted of ACT and NACT applied at concentrations of 30 ml and 60 ml, along with a control. Plant growth parameters, including plant height and root length, were observed during the early growth phase (2–7 days after planting). The results showed that compost tea application significantly affected maize growth during the early growth stage (P < 0.05). Aerated compost tea generally produced better growth responses than non-aerated compost tea, particularly at lower concentrations. The ACT treatment at 30 ml resulted in the highest plant height and root length, while higher concentrations, especially NACT at 60 ml, tended to suppress plant growth. These findings indicate that compost tea primarily functions as an early growth stimulant and that excessive application may reduce its effectiveness. In conclusion, aerated compost tea at low concentrations is more effective in promoting early maize growth than non-aerated compost tea. Proper optimization of compost tea concentration and application strategy is essential to maximize its benefits within sustainable agricultural systems.